2015
DOI: 10.1074/jbc.m114.604678
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function Analysis of Nucleocapsid Protein of Tomato Spotted Wilt Virus Interacting with RNA Using Homology Modeling

Abstract: Background:The crystal structure of viral proteins is not available for many plant viruses including tomato spotted wilt virus (TSWV). Results: By homology modeling, we mapped the RNA binding sites and discovered a protective feature of TSWV nucleocapsid (N). Conclusion: Homology modeling provided a basis for functional analysis of TSWV N interacting with RNA. Significance: This approach might be applicable for other plant viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
0
2

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 37 publications
7
49
0
2
Order By: Relevance
“…This finding was consistent with recent data from TWSV and Bunyamwera virus (BUNV) studies [11,16]. Study on TWSV N protein showed that it could bind nonspecifically to E. coli cellular RNA [11].…”
Section: Rna-binding Sites On Npsupporting
confidence: 91%
See 4 more Smart Citations
“…This finding was consistent with recent data from TWSV and Bunyamwera virus (BUNV) studies [11,16]. Study on TWSV N protein showed that it could bind nonspecifically to E. coli cellular RNA [11].…”
Section: Rna-binding Sites On Npsupporting
confidence: 91%
“…This finding was consistent with recent data from TWSV and Bunyamwera virus (BUNV) studies [11,16]. Study on TWSV N protein showed that it could bind nonspecifically to E. coli cellular RNA [11]. Study on BUNV suggested that N protein did not obligatorily require a sequence or structure for RNA encapsidation because neither common linear sequence nor structure was present in the extracted RNAs bound to RNPs [16].…”
Section: Rna-binding Sites On Npsupporting
confidence: 89%
See 3 more Smart Citations